PERILAKU PENGGUNAAN TERAPI KOMPLEMENTER PADA PASIEN KANKER YANG SEDANG MENJALANI PENGOBATAN (STUDI KUALITATIF) - Werdani, Yesiana Dwi Wahyu; Sari, Nia Novita (JPK : Jurnal Penelitian Kesehatan, 2025)
Cancer is a disease that easily metastasizes. This disease requires various modalities of therapy to minimize the spread. Side effects of cancer treatment can arise physically and mentally which often disrupt the patient's life. This triggers patients to try complementary therapy, although not all patients undertake this effort. This study aims to explore the behavior of using complementary therapy in cancer patients undergoing cancer treatment. This study has a qualitative design with a phenomenological approach. The population is all cancer patients living at the Indonesian Cancer Foundation East Java Branch who are undergoing cancer treatment in the form of surgery/chemotherapy/radiation/chemoradiotherapy. A sample of 22 people was taken using the snowball sampling technique. Data collection was carried out through in-depth interviews, followed by data transcription and coding to group the themes found. The results of the study obtained two major themes: theme 1 medical therapy is the main choices, with a sub-theme that medical therapy is better than complementary therapy. Meanwhile, theme 2, complementary therapies, complement medical therapy, identified two sub-themes: herbal complementary therapies are good for reducing the side effects of cancer treatment, and non-herbal complementary therapies can increase the body's positive response. Conclusion: Cancer patients have different perspectives on medical treatment and complementary therapies. The use of complementary therapies is driven by the need for cancer patients to reduce the side effects of treatment and increase their body's positive response.